Meningkatakan Motorik Halus Anak Usia Dini Melalui Seni Melipat Kertas di Tk Al-Mubarak Tonrorita di Kecamatan Biringbulu Kabupaten Gowa - Uswatun Hasanah; Tasrif Akib; Musfira Musfira (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
The problem in this study is the lack of play activities that stimulate children's fine motor skills at TK Almubarak Tonrorita Kec.Biringbulu, Gowa Regency. This study aims to improve fine motor skills in early childhood through paper folding activities. The type of research used is Classroom Action Research which consists of two cycles where each meeting is held three times. The research procedure includes planning, implementation, observation, and reflection. The subjects of this study were group A children of TK Almubarak Tonrorita, Biringbulu District with a total of 15 children consisting of boys and girls. The data collection techniques used are observation sheets and documentation. The data analysis used is descriptive qualitative. Each cycle I and II has increased. The results showed that cycle I of 15 children in improving fine motor skills through paper folding activities obtained an average value of children in the criteria for starting to develop (MB), while in cycle II the average child obtained the ability to develop very well (BSB) criteria. Based on the results of the research above, it can be concluded that the development of fine motor skills of early childhood in Almubarak Tonrorita Kindergarten, Biringbulu District, Gowa Regency through paper folding activities has increased.